PENGARUH BREATHING RELAXATION DENGAN TEKNIK BALLOON BLOWING TERHADAP SATURASI OKSIGEN PASIEN PPOK - tunik tunik; Rahayu Niningasih; Edi Yuswantoro (Poltekkes Kemenkes Malang, 2020)
Physiology and psychology are problems which statistically experienced by the patients of COPD and decrease their quality of life. Breathing Relaxation with Balloon Blowing Technique is one the best breathing exercises to regain the function of lungs. The objective of this thesis was to measure the effectiveness of breathing relaxation with balloon blowing technique towards oxygen saturation. The research design used in this thesis was pre experiment with pre post test one design. The sample of the thesis was thirty respondents of COPD patients of Flamboyan room in dr. Soedomo hospital. The sampling technique used in this research was consecutive sampling technique. It was consisted of a group of intervention. Pre test and post test were used to collect the data of the research on the third and seventh day. The result were tested using Repeated ANOVA test. The research showed that there was a significant result to oxygen saturation, before and after doing intervention on the third and seventh day. The result of statistical analysis showed the p value was smaller than 0.05 at the oxygen saturation, on the third and seventh day. Breathing relaxation with balloon blowing technique can increase the oxygen saturation patient with COPD